Localized surface plasmon resonance in Au nanoprisms on glass substrates - Lopatynska, O.G.; Lopatynskyi, A.M.; Borodinova, T.I.; Chegel, V.I.; Poperenko, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Metal nanocrystals are actual objects for the modern biophysics mainly because of their usage in sensors based on localized surface plasmon resonance (LSPR) and as active substrates for surface-enhanced spectroscopies. This work deals with the experimental and theoretical investigation of optical properties of trigonal and hexagonal Au nanoprisms deposited on the glass substrates. It was confirmed for the studied structures that the LSPR spectra depend on the crystals shape and size. Theoretical modeling the optical properties of plasmon-supporting nanoprisms was performed using the finite-difference time-domain method. The experimentally obtained and theoretically modeled LSPR spectral positions were found to be different, which can be attributed to a high spread of nanoprism shapes and sizes in the same sample and to nanocrystals aggregation effect confirmed by microscopy data. Additionally, the distributions of the electric field in the vicinity of nanoprisms under the LSPR conditions were simulated, and a strong field intensity enhancement at the corners of the prisms was demonstrated, which implies the promising application of such plasmonic nanostructures for surfaceenhanced spectroscopy.